Pembelajaran Energi Terbarukan Berbasis Praktikum Untuk Mengembangkan Karir Vokasional: Analisis Bibliometrik Pada Tahun 2015-2024 - Irfan, Agus; Irwanto, Irwanto; Suhendar, Suhendar; Widyaningsih, Mia (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to identify the development and understanding of the role of laboratory-based renewable energy education in vocational career development. This research employs bibliometric analysis using the Scopus database with the assistance of Biblioshiny and VOSviewer tools. From 2015 to 2024, 64 documents were found in Scopus and filtered down to 63 documents, comprising articles, book chapters, and conference papers relevant to the keywords